Identification of Medicinal Plants In The Environment of Universitas Pahlawan Tuanku Tambusai - Awari Susanti; Zurrahmi Z.R; Endang Mayasari; Erma Kusumayanti (Universitas Pahlawan Tuanku Tambusai, 2025)
The research identification of medicinal plants was conducted in the environment of Universitas Pahlawan Tuanku Tambusai. Riau community has long known and utilized medicinal plants as traditional medicines, these medicinal plants have been used in traditional medicine for generations as an effort to maintain health, prevent disease, and care for health. Traditional medicinal plants serve as primary materials for traditional medicines and are acknowledged for their health benefits. The aim of this study was to classify medical plant species of medicinal plants. Data collection involved surveys and interviews, and the classification was carried out using herbarium methods. The results identified 20 species of medicinal plants across 14 families. Predominantly, these families were associated with the Zingiberaceae family, encompassing species such as Curcuma Domestica, Curcuma Xontoriza, Kaempferia Galanga, Renguas Galanga, Zingiber Officinale, Costus Speciosus. Parts of the plant used as medicine vary depending on the type of plant, the most widely used plant organs are leaves, rhizomes and roots.